Assessment of pain in chronic renal failure patients going through hemodialysis - Fabiana Larissa Barbosa da Silva; Geórgia Alcântara Alencar Melo; Regilane Cordeiro dos Santos; Renan Alves Silva; Letícia Lima Aguiar; Joselany Áfio Caetano (Universidade Federal do Ceará, 2020)
Objective: to assess the pain and the differences of this assessment with social, economic and clinical variables in individuals with chronic kidney disease. Methods: cross-sectional study, with 90 patients with hemodialysis clinics. Three instruments were used clinical/sociodemographic, visual analogue pain scale and McGill pain questionnaire. Mann-Whitney and Kruskal-Wallis U tests were used. Results: the most frequent kind of pain was musculoskeletal (35.6%), which was classified as moderate by using the visual analogue pain scale. In McGill's questionnaire, the most selected categories were sensory and affective, which characterize pain as acute and thin. Significant statistical differences in medians of pain were found with family income, source of income, use of analgesics/anti-inflammatories, use of acupuncture and impaired sleep. Conclusion: pain was a recurrent result in various regions of the body among patients with chronic renal failure.